Chemical Composition of Coir Fiber (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The shell of the cocoon consists of a thin fiber, which is called silk fiber. Silk fiber is a thick, stretchy liquid in the body of the worm and is produced by a special gland.The silk gland is a pair of tubular organs located on both sides of the worm body cavity. Each side of the gland begins with a septum, followed by a fluid bladder, connected to the fluid bladder by pairs of silk ducts, which in turn merge into a single odd silk duct. The dark silk road is located in the head of the worm, and its outer end connects to the silk tube located in the middle of the lower lip in the mouth apparatus, and the silk liquid comes out from here. The silk that comes out consists of two fibers, and these fibers are firmly attached to each other.There is a compression device in the middle of the odd silk path, with the help of which the thickness and thickness of the silk that the worm separates for wrapping the cocoon is controlled to a certain extent under the influence of temperature.